Efeitos do déficit hídrico sobre alguns aspectos biofísicos, bioquímicos e no desenvolvimento do feijão-vagem (Phaseolus vulgaris L.) - Freire, Antonio Lucineudo de Oliveira (1990)
The purpose of this experiment was to verify the effects of the water deficit in french beans plants. The assay was conducted in a glass-house at the Department of Biology of the Escola Superior de Agricultura de Lavras (MG), using. Two cultivars (Macarrão Rasteiro and Verde Baixo). The water deficit was imposed at three distincts phases of the biocycle: vegetati-ve growth, flowering and frutification. The water stress consisted of the withholding irrigation at the cited phases, evaluating then the recovery after irrigation. The development of the water deficit caused, in the cultivars and phases of the. cycle studied a progressive reduction of the leaf water potential, relative water content, stomatal conductance, transpiration rate, nitrate reductase activity and protein content. It was noted that those characteristics showed a gradual recovery after irrigation, except the nitrate reductase activity in the Macarrão Rasteiro cultivar. The leaf temperature incrased in the Macarrão Rasteiro cultivar, when the water stress was imposed in the phases of vegetative growth and frutification and,. in the Verde Baixo cultivar, during the phases of flowering and frutification. Increases of the total amino acid had been noted in both cultivars. The total soluble sugars and reducing sugars concentrations suffered an increase, in the Macarrão Rasteiro cultivar, only at the flowering and, in the Verde Baixo cultivar, at the vegetative growth. The water stress at the vegetative growth reduced the shoot dry matter content, the number of flowers, pods per plant and pods weight, showing that this phase as being the most sensitive to the water deficit. The Macarrão Rasteiro cultivar appeared to be more tolerant to the stress.